Effect of Nutritional Status in Postoperative Recovery among Surgical patients - Zulfiqar Ali, Shafique-Ur-Rehman, Muhammad Aamir Jameel, Haroon Javaid Majid (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To draw a comparison between the frequencies of postoperative complications between malnourished and well-nourished patients and to determine the impact of pre-operative nutritional-status on the postoperative recovery among surgical patients. Place and duration of study: This was a cross sectional comparative observational study by design which was conducted in the Department of Surgery, Shaikh Zayed Hospital Lahore Pakistan form June 2014 to December 2014. Study Design: Cross sectional comparative study. Methodology: Four hundred volunteer individuals were taken in the study. Written, informed consent was taken from all the included individuals. All the included individuals were weighed by a digital scale and their heights were measured using the height scale, and thus their Body Mass Index was calculated according to the following formula, before the surgery; BMI less than 18 or more than 25 and was considered as Malnutrition. Also Hemoglobin, TLC (Total Lymphocyte count = % Lymphocytes X WBC/ 100),serum albumin was measured and if found impaired, patient was considered to have under-nutrition. Now after surgery the patients were followed for 5 days postoperatively and any complication was noted. Occurrence of any single complication was treated as presence of complication. Total number of days stayed at hospital postoperatively were also calculated. Data was analyzed using SPSS 20. Results: There was significant difference with respect to major complications and side effects between well-noursihed and malnourished cases. More number of cases developed infection in the malnourished groups as compared to other group. Conclusion: Patients must be kept under observation for their nutritional status postoperatively for a specific duration so that morbidities could be reduces and patients can get back to work earlier. Keywords: Malnourish, Surgical Patients, Nutritional Assessment, BMI